2010
DOI: 10.1038/ijo.2010.187
|View full text |Cite
|
Sign up to set email alerts
|

Association between the APOA2 promoter polymorphism and body weight in Mediterranean and Asian populations: replication of a gene–saturated fat interaction

Abstract: ObjectiveThe APOA2 gene has been associated with obesity and insulin resistance (IR) in animal and human studies with controversial results. We have reported an APOA2-saturated fat interaction determining body mass index (BMI) and obesity in American populations. This work aims to extend our findings to European and Asian populations.MethodsCross-sectional study in 4602 subjects from 2 independent populations: A high cardiovascular risk Mediterranean population (n=907 men and women; aged 67+/−6 years) and a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 42 publications
6
82
2
Order By: Relevance
“…The sample size was determined to allow detection of a 20% difference in mean serum concentration of at least one oxidative stress factor between the groups, with an α error of 0.05 and a β power of 80%. On the basis of the results obtained in the previous studies, similar effects have been found for TT and TC genotypes (Corella et al, 2007(Corella et al, , 2009(Corella et al, , 2011. Therefore, the patients were subdivided into two groups, homozygous for the allele C (CC) and the T-allele carriers (TT/TC), according to different genotypes of ApoA-II.…”
Section: Methodsmentioning
confidence: 59%
“…The sample size was determined to allow detection of a 20% difference in mean serum concentration of at least one oxidative stress factor between the groups, with an α error of 0.05 and a β power of 80%. On the basis of the results obtained in the previous studies, similar effects have been found for TT and TC genotypes (Corella et al, 2007(Corella et al, , 2009(Corella et al, , 2011. Therefore, the patients were subdivided into two groups, homozygous for the allele C (CC) and the T-allele carriers (TT/TC), according to different genotypes of ApoA-II.…”
Section: Methodsmentioning
confidence: 59%
“…The apolipoprotein A-II (APOA2) -265 T>C promoter functional polymorphism appears to interact with high-saturated fat to increase BMI and obesity risk in several independent populations (Mediterranean, Asian, Caucasian, Hispanic and Caribbean) [138,139]. High-saturated fat intake was associated with significant increases in the genetic risk for obesity across populations [139].…”
Section: Obesity-predisposing Gene Variants Interact With Dietmentioning
confidence: 99%
“…These results were replicated for the first time in three independent populations (Corella et al, 2009). Subsequently, the authors replicated this interaction in Mediterranean and Chinese populations (Corella et al, 2011) confirming the importance of genetic modulation by dietary factors, and also the need to replicate gene-diet interactions to increase the scientific evidence and finally to contribute to personalize diet based on genetic susceptibility.…”
Section: Results From Observational Studiesmentioning
confidence: 83%